Clinical assessment and patient education of chemical intolerance - Ravi, Tharani; Johnson-Esparza, Yajaira; Hernandez, Jessica; Andry, Nehman; Ali, Fozia; Del Pilar Montanez Villacampa, Maria; Rincon, Rudolfo; Perales, Roger; Palmer, Raymond F. (International Journal Of Community Medicine And Public Health, 2024)
Chemical intolerance (CI) is characterized by multi-system symptoms initiated by a one-time high dose or persistent low-dose exposure to environmental toxicants. Symptoms of this “medically unexplained illness” often include fatigue, headache, weakness, rash, mood changes, musculoskeletal pain, gastrointestinal, difficulties with memory, concentration, and respiratory problems. A general disease mechanism called toxicant-induced loss of tolerance (TILT) explains the initiation, symptoms, and intolerances to chemicals, foods, and medicines reported worldwide by individuals with this condition. TILT is a 2-stage disease process initiated by a major chemical exposure, or a series of low-level exposures, followed by multisystem symptoms and onset of new intolerances. Despite its prevalence of up to 20%, most primary care physicians are not aware of this disease process and thus have been unable to recognize patients with CI. This case series describes three family medicine clinic patients who had multisystem symptoms that were triggered by chemical exposures, saw multiple specialists with no improvement, who were eventually diagnosed with CI and went through a behaviorally based avoidance education program. This report describes the impact of a coordinated educational intervention for patients with CI. We offer several educational tools for health practitioners to discuss with their patients. These patient stories highlight the importance for physicians to be knowledgeable about CI in order to facilitate symptom reduction and improve the quality of life for these patients.